2008
DOI: 10.1021/jp8013783
|View full text |Cite
|
Sign up to set email alerts
|

Poly(amidoamine) Dendrimers on Lipid Bilayers II: Effects of Bilayer Phase and Dendrimer Termination

Abstract: The molecular structures and enthalpy release during binding of poly(amidoamine) (PAMAM) dendrimers to 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) bilayers were explored through atomistic molecular dynamics. Three PAMAM dendrimer terminations were examined: protonated primary amine, neutral acetamide, and deprotonated carboxylic acid. Fluid and gel lipid phases were examined to extract the effects of lipid tail mobility on the binding of generation-3 dendrimers, which are directly relevant to the nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
120
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(140 citation statements)
references
References 44 publications
17
120
1
2
Order By: Relevance
“…EC50 for HaCaT cell line and SW480 cell line was about 30 μg/mL and 20 μM respectively for G4-HN2, compare with hNPCs which was 6.17 μg/mL (Bielawski et al, 2011). Reactions of positively charged nanoparticles with lipid bilayer of cellular membrane may result in nano-scale hole formation in the membrane layers, allowing molecular transport across the membranes (Thiagarajan et al, 2013;Hong et al, 2004Hong et al, , 2006Mecke et al, 2005;Martin et al, 2007;Kelly et al, 2008aKelly et al, , 2008b. Moreover, uptake of positively charged PAMAM-NH 2 of hNPCs was proved in our study (Fig.…”
Section: A B C Dsupporting
confidence: 63%
“…EC50 for HaCaT cell line and SW480 cell line was about 30 μg/mL and 20 μM respectively for G4-HN2, compare with hNPCs which was 6.17 μg/mL (Bielawski et al, 2011). Reactions of positively charged nanoparticles with lipid bilayer of cellular membrane may result in nano-scale hole formation in the membrane layers, allowing molecular transport across the membranes (Thiagarajan et al, 2013;Hong et al, 2004Hong et al, , 2006Mecke et al, 2005;Martin et al, 2007;Kelly et al, 2008aKelly et al, , 2008b. Moreover, uptake of positively charged PAMAM-NH 2 of hNPCs was proved in our study (Fig.…”
Section: A B C Dsupporting
confidence: 63%
“…The increased layer spacing was attributed to dendrimers embedding in the water shells between bilayers or increased electrostatic repulsion between the layers caused by embedded dendrimers. At 46°C a larger bilayer spacing suggested shape change of dendrimers when interacting with gel/liquid crystalline phases, as observed in MD simulations from Kelly et al [116] and discussed further in Section 4.4. In summary, liposomes have been used as model membranes in a number of studies to investigate their interactions with PAMAM dendrimers.…”
Section: Thermodynamic Insights: Effect Of Dendrimers On Membrane Flumentioning
confidence: 61%
“…The functionalisation of the dendrimer has been found to change its overall shape and rigidity, which in turn influences its interactions with a flexible membrane. The amine-terminated dendrimers can deform against a bilayer or substrate as suggested by computational studies [116] and observed through AFM [117,118], reducing the structural disruption of the bilayer. .…”
Section: Thermodynamic Insights: Effect Of Dendrimers On Membrane Flumentioning
confidence: 98%
“…Kelly et al have investigated the interactions between G3 PAMAM dendrimers and DMPC bilayers in gel and liquid phase by MD simulations [23]. As they describe, dendrimers have nearly spherical shape when interacting with gel phase lipids, but when interacting with fluid phase lipids they are flattened on the bilayer surface, moreover they enter in the alkyl chain region.…”
Section: Changes In Thermal Behaviormentioning
confidence: 99%
“…The interaction between cell membranes and nanocarriers, such as dendrimers, is very important, because in the most cases carriers have to get across the lipid bilayer without disrupting it. Previous studies based on atomic force microscopy (AFM) [12][13][14][15][16][17] isothermal titration calorimetry (ITC), fluorescence correlated spectroscopy (FCS) [17][18], in vitro experiments [13,[19][20] and molecular dynamics simulations (MD) [14,17,[21][22][23][24] showed that cationic dendrimers disrupt lipid bilayers by forming holes on the bilayer surface and may remove lipids from it. The degree of the disruption depends on the size and charge of the dendrimer.…”
Section: Introductionmentioning
confidence: 99%